2018
DOI: 10.20961/jkpk.v3i3.23308
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of High School Students’ Argumentation Ability in the topic of Buffer Solution

Abstract: <div class="WordSection1"><p>Argumentation is scientific discourse in science learning that is used as a link between knowledge from an environment and concepts in science learning. Through argumentation skills can be controlled student understanding in connecting facts with concepts in learning. This study aims to analyze students' argumentation ability on buffer solution subject. Students' argumentation ability is divided into 4 levels; level 1 (claims), level 2 (claims with data), level 3 (claim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 2 publications
2
20
0
3
Order By: Relevance
“…It was categorized low. Previous researchers [55], [56] found that sharing reasons and data should be supported with concepts or theories the students studied previously. One hundred two students felt the confidence to rebuttal any inaccurate arguments (item 9).…”
Section: The Students' Perceptions Concerning the Argumentative Scien...mentioning
confidence: 91%
“…It was categorized low. Previous researchers [55], [56] found that sharing reasons and data should be supported with concepts or theories the students studied previously. One hundred two students felt the confidence to rebuttal any inaccurate arguments (item 9).…”
Section: The Students' Perceptions Concerning the Argumentative Scien...mentioning
confidence: 91%
“…Keterampilan argumentasi sangat penting untuk dikuasai siswa, karena keterampilan argumentasi mencakup 2 keterampilan penting abad 21, yakni keterampilan berikir kritis (critical thingking skill) dan keterampilan berkomunikasi (communication skill) (Devi et al 2018).…”
Section: Pendahuluanunclassified
“…Inti dari argumentasi ilmiah adalah membangun suatu pernyataan atau klaim yang didasarkan pada bukti-bukti ilmiah (Faize et al, 2017). Berdasarkan hasil beberapa penelitian yang telah dilakukan untuk mendeskripsikan profil kererampilan argumentasi ilmiah siswa di beberapa daerah menunjukkan bahwa keterampilan argumentasi ilmiah siswa di Indonesia masih tergolong rendah (Devi et al, 2018;Putri & Rusdiana, 2017;Wahdan et al, 2017).…”
Section: Pendahuluanunclassified
“…Hal ini berarti siswa telah memiliki kemampuan yang cukup baik dalam mengutarakan pernyataan atau pendapat mereka terkait fenomena yang disajikan pada soal, tetapi masih terkendala dalam hal menuliskan alasan seperti bukti, fakta, menghubungkan data dengan klaim, dan menyertakan asumsi atau teori dapat yang membenarkan warrant dan mendukung claim. Hasil yang diperoleh ini memiliki kesamaan dengan temuan dari beberapa penelitian sebelumnya yaitu argumen siswa yang paling banyak ditemukan adalah argumen yang didominasi oleh claim saja (Devi, Susanti VH, & Indriyanti, 2019). Siswa hanya mampu memberikan jawaban berupa claim namun belum disertai alasan yang menghubungkan pernyataannya dengan bukti ilmiah (Handayani, Murniati, & Sardianto, 2015).…”
Section: Metode Penelitianunclassified